Perfil nutricional e de atividade física de idosos: um estudo de revisão - De Souza, Vinicius Cunha (Brasil, 2022)
Introduction: The aging process is a natural process and inherent to the human being, with a growing increase in the elderly population in society. In this scenario, there are declines in functional capacity, postural changes, loss of muscle mass, mobility, balance and coordination. Health promotion, through the practice of physical activity and/or physical exercise combined with an adequate nutritional profile and status for the elderly population is essential to reduce the losses arising from the senescence process and increase the level of physical fitness, quality of life and increased life expectancy of the elderly population. Objective: To analyze the nutritional and physical activity profile of the elderly. Method: Methods: A systematic literature review was carried out through searches in Pubmed, Scielo, academic google and Lilacs databases, with the following search terms: Nutritional profile of the elderly, nutritional profile and physical activity in the elderly, nutritional profile of the elderly, nutritional and physical activity profile in the elderly. Results: After searching and selecting articles in the literature, 7 studies were selected for review. Conclusion: Eutrophic elderly people have adequate levels of muscle mass and adequate intake of macronutrients, as well as an adequate level of physical activity for their age. Frail elderly, underweight or overweight, sedentary and/or physically inactive have higher levels of frailty and low functionality compared to eutrophic elderly and do not have adequate macro and micro nutrients intake compared to eutrophic elderly